Organizational ambidexterity at INTRA-NPD level of analysis with quality - innovation matrix - Ahmad Zaidi, Mohamad Faizal (UUM College of Business, 2017)
Organizational ambidexterity refers to the firm’s capacity to simultaneously exploit existing product offerings with familiar knowledge, and explore new product opportunities with unfamiliar knowledge.Due to this definition, ambidexterity has been commonly studied at inter-new product development (NPD) level.As such, studies at the intra-NPD (in a single NPD) are still rare. Although both exploitative and explorative are critical capabilities for NPDs, with limited resources at hands, most firms will have to do a trade-off between them. As a result, while some firms preferred exploitative NPD, some others have adventured into explorative NPD.Therefore, a single NPD project is the feasible option to most firms at any one time. Although quality is the focus in exploitative NPD, while innovation is the emphasis in explorative NPD, both are imperative to any types of NPD.Thus, it was suggested firm that is capable of creating balance between quality and innovation in a single NPD will be more successful than the others at sustaining competitive advantage.However, creating a balance between quality and innovation in a single NPD is a challenging effort. As a result, this article proposed a quality-innovation (Q-I) matrix to demonstrate the concept of organizational ambidexterity for creating balance between quality and innovation in a single NPD. The Q-I matrix will enhance our understanding on the concept of organizational ambidexterity at intra-NPD level, which is still rarely studied in contrast to the inter-NPD level of analysis.